Seasonal changes in diet selectivity and grazing behaviour of goats on semi-arid rangeland - BHAITA, RAGHAVENDRA; SANKHYAN, S K; SHINDE, A K; VERMA, D L (The Indian Journal of Animal Sciences, 2014)
Dietary preference and grazing behaviour of male Kutchi goats grazed on semi-arid rangeland were continuously monitored from 08: 00 to 17: 00 hr, during monsoon, winter and summer. Crude protein (CP), neutral detergent fibre (NDF) and acid detergent fibre (ADF) contents of pasture were 9.94, 72.45 and 52.86 % in monsoon, 7.19,67.76 and 54.42 % in winter and 6.61, 73.75 and 64.55 % in summer, respectively. CP content of diet in monsoon was 13.40 %, which slightly declined to 12.78 % in winter, and again increased to 14.84 % in summer. Preference index (PI) for CP progressively increased from 1.35 in monsoon to 1.78 in winter and 2.25 in summer. Grazing period was 7.41 hr in monsoon, 8.46 hr in winter and 8.07 hr in summer, and it was negatively correlated with ambient temperature (r = -0.76) and relative humidity (r= -0.34). Masticating rate (chew/min) was almost similar in 3 seasons and average value was 76. Ruminating rate was 1.44, 1.11 and 1.08 in monsoon, winter and summer, respectively. The bipedal stance was lowest in monsoon (0.52), highest in winter (2.86) and intermediate in summer (1.25). It is concluded that goats grazing on semiarid rangeland select quality nutrients with deterioration of pasture condition and alter behavioural pattern to minimize the environmental stress.